2001
DOI: 10.1046/j.1523-1755.2001.00934.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of heparanase in puromycin aminonucleoside nephrosis

Abstract: The previously mentioned data confirm that the novel beta-D-endoglycosidase heparanase is up-regulated and activated in glomeruli from rats with proteinuria. Heparanase may be involved, therefore, in the loss of glomerular charge seen in proteinuria. Moreover, the presence of heparanase in normal tubules suggests that it may also be involved in cell migration or turnover.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
68
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 27 publications
3
68
0
Order By: Relevance
“…Our study demonstrates that heparanase expression is increased in AN and correlated with the loss of HS in the GBM, suggesting that heparanase may play an important role in HS reduction. The increased expression of heparanase in AN is in line with the findings in puromycin aminonucleoside nephrosis, passive Heymann nephritis, and anti-GBM nephritis (15)(16)(17)(18). The loss of glomerular HS also is in accordance with previous studies in proteinuric renal disease (7)(8)(9).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study demonstrates that heparanase expression is increased in AN and correlated with the loss of HS in the GBM, suggesting that heparanase may play an important role in HS reduction. The increased expression of heparanase in AN is in line with the findings in puromycin aminonucleoside nephrosis, passive Heymann nephritis, and anti-GBM nephritis (15)(16)(17)(18). The loss of glomerular HS also is in accordance with previous studies in proteinuric renal disease (7)(8)(9).…”
Section: Discussionsupporting
confidence: 90%
“…A recent study in patients with diabetic nephropathy suggested that loss of HS in the GBM is attributable to accelerated HS degradation by increased heparanase expression (14). Studies in experimental renal diseases (passive Heymann nephritis, puromycin aminonucleoside nephrosis, and anti-GBM nephritis) suggest that heparanase also may be involved in nondiabetic proteinuric disease (15)(16)(17)(18).…”
mentioning
confidence: 99%
“…In the past 5 years, upregulation of glomerular heparanase gene expression has been shown in numerous clinical or experimental nephropathies such as puromycin aminonucleoside nephrosis [30], passive Heymann nephritis [31], anti-GBM nephritis [32], adriamycin nephropathy [33], streptozotocin-induced diabetic nephropathy [11], minimal change nephrotic syndrome, and membranous glomerulopathy [34]. The molecular mechanisms that regulate heparanase gene expression and activity still have to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Heparanase up-regulation has been documented in a variety of human tumors correlating, in some cases, with increased vascular density and poor postoperative survival (14 -17). Heparanase overexpression has also been noted in several other pathologies such as cirrhosis (18), nephrosis (19), and diabetes (20). In addition to its intimate involvement in the egress of cells from the blood stream, heparanase activity may release a multitude of HS-bound, extracellular matrix-resident growth factors, cytokines, chemokines, and enzymes that might profoundly affect cell and tissue function (1,21).…”
mentioning
confidence: 99%